Fall-Related Psychological Concerns and Anxiety among Community-Dwelling Older Adults: Systematic Review and Meta-Analysis. - Marie-Christine Payette; Claude Bélanger; Vanessa Léveillé; Sébastien Grenier (PLoS ONE, 2016)
Fear of falling and other fall-related psychological concerns (FRPCs), such as falls-efficacy and balance confidence, are highly prevalent among community-dwelling older adults. Anxiety and FRPCs have frequently, but inconsistently, been found to be associated in the literature. The purpose of this study is to clarify those inconsistencies with a systematic review and meta-analysis and to evaluate if the strength of this relationship varies based on the different FRPC constructs used (e.g., fear of falling, falls-efficacy or balance confidence). A systematic review was conducted through multiple databases (e.g., MEDLINE, PsycINFO) to include all articles published before June 10th 2015 that measured anxiety and FRPCs in community-dwelling older adults. Active researchers in the field were also contacted in an effort to include unpublished studies. The systematic review led to the inclusion of twenty relevant articles (n = 4738). A random-effect meta-analysis revealed that the mean effect size for fear of falling and anxiety is r = 0.32 (95% CI: 0.22-0.40), Z = 6.49, p < 0.001 and the mean effect size for falls-efficacy or balance confidence and anxiety is r = 0.31 (95% CI: 0.23-0.40), Z = 6.72, p < 0.001. A Q-test for heterogeneity revealed that the two effect sizes are not significantly different (Q(19) = 0.13, p = n.s.). This study is the first meta-analysis on the relationship between anxiety and FRPCs among community-dwelling older adults. It demonstrates the importance of considering anxiety when treating older adults with FRPCs.